HIV antiretroviral therapy drugs induce premature senescence and altered physiology in HUVECs. (October 2018) - Cohen, Justin; D'Agostino, Luca; Tuzer, Ferit; Torres, Claudio
Highlights: The NRTIs TDF and FTC induce premature senescence in HUVECs. Senescent HUVECs possess an inflammatory response and oxidative stress. Senescent HUVECs have altered eNOS activation. Senescent HUVEC conditioned media induces premature senescence in astrocytes. Abstract: Developments in medicine have led to a significant increase in the average human lifespan. This increase in aging is most readily apparent in the case of HIV where antiretroviral therapy has shifted infection from a terminal to a chronic but manageable disease. Despite this advance, patients suffer from co-morbidities best described as an accelerated aging phenotype. A potential contributor is cellular senescence, an aging-associated growth arrest, which has already been linked to other HIV co-morbidities such as lipodystrophies and osteoporosis in response to antiretroviral drugs. We have previously demonstrated that astrocytes senescence in response to antiretroviral drugs. As endothelial cells play a critical role regulating the blood brain barrier (BBB) and senescence could severely impact barrier permeability, we investigate the role of a commonly used combination of HIV reverse transcriptase inhibitors on the senescence program of human umbilical vein endothelial cells (HUVECs). Our studies indicate that HUVECs underwent premature senescence associated with inflammation, oxidative stress and altered eNOS activation. Treated cells had detrimental paracrine effects on astrocytes including paracrine senescence, suggesting that senescent HUVECs could influence astrocytes, which line the other side of the BBB. These results may have implications for HIV-associated neurocognitive disorders (HAND), a set of neurological deficits.